The Possibilities for "Humanizing" Posthumanist Inquiries: An Intra-Active Conversation. (October 2020) - Dernikos, Bessie P.; Ferguson, Daniel E.; Siegel, Marjorie
What are the ethical responsibilities of doing and teaching qualitative inquiry at a time when Black and Brown bodies are under assault, an expression of White supremacy that has become ever more visible in the wake of the election of Donald Trump? And how might scholars who "think with" posthumanist theories respond to the call for more "humanizing" methodologies being made by African American and Latinx researchers? This article responds to this moment by presenting a conversation among three literacy scholars about the ethical challenges they have encountered in their own engagements with posthumanist theories, and the implications this has for doing/teaching qualitative inquiry. We call for more openness about the limits as well as the possibilities of posthumanisms, and more attention to ethics for justice. The entanglements of human/nonhuman assemblages in these dangerous times call on us to act, not only think, with theory.